Trends and Challenges in Aviation English: A Literature Review in English for Specific Purposes - Dumdumaya, Ma. Theresa (Journal of Natural Language and Linguistics, 2025)
This paper examines the progress and ongoing issues in Aviation English, using the perspective of English for Specific Purposes (ESP). It focuses on language, teaching, technology, and cultural understanding. Employing an integrative approach, the review systematically synthesizes the results of peer-reviewed studies, reports, and authoritative articles based on their year of issue to reflect a modern-day scenario. The findings are categorized into three themes: specialized communication needs, intercultural competence, and pedagogical innovations, including the use of corpus-based resources and mobile applications. Remaining challenges were also noted, including insufficient teaching resources, shortfalls in teacher training, and the inadequacy of standardized testing, including ICAO’s Language Proficiency Requirements. Future studies should use content that fits the culture, better ways to assess, and include views from people within the industry. By establishing cross-disciplinary collaborations that identify and formulate training based on industry needs, English-language aviation education can be an effective formal education contribution to international communications, safety, and inclusivity in aviation.